DUOLINGO APP EFFECT ON ARABIC SPEAKING SKILLS (Jurnal Sosial Humaniora dan Pendidikan, 2022)
Arabic is a very special language. In addition to being the language of the holy book of the al-Qur'an, Arabic is also an international language agreed upon by the United Nations. However, not many people can communicate or speak Arabic in Indonesia. Many factors are the cause, such as a lack of vocabulary savings and not being used to speaking Arabic. From the emergence of these problems, it raises the question of how to make many people who have a lot of Arabic vocabulary so that they can speak Arabic fluently. To overcome this problem, the author conducted a study on the effect of using Duolingo application as a media innovation to improve Arabic speaking skills. The author uses a survey method by giving several questions to fifteen respondents from the Cipulus Wanayasa Islamic Boarding School students as a tool to collect data. The results showed that 74.6% respondents' answers agreed that Duolingo application had an effect on improving Arabic speaking skills and 25.4% respondents' answers gave an ordinary opinion that had no effect. From the results, the authors can conclude that there is an effect of Duolingo application for improving students' Arabic speaking skills. This application is very useful for those who want to learn Arabic on their own.